Malaysian commercial banks: Do income smoothing, capital management, signaling, and pro-cyclicality exist through loan loss provisions? - Abdul Adzis, Azira; Anuar, Herman Shah; Mohd Hishamuddin, Noor Shahieda (ARPN Publishers, 2015)
Existing literature argues that loan loss provisions are subject to managerial discretion and commonly associated with the issues of income smoothing, capital management, signaling and pro-cyclicality.The main objective of this study is to examine the evidence of income smoothing, capital management, signaling, and pro-cyclical behavior through loan loss provisions of Malaysian commercial banks for period 2002-2012.Using a sample of 15 commercial banks, the results indicate that Malaysian commercial banks do smooth income through loan loss provisions while on the other hand, no conclusive evidence to support that Malaysian commercial banks manage capital through loan loss provisions.As for the signaling and pro-cyclicality, no concrete evidence to support Malaysian commercial banks engages in signaling activities and pro-cyclicality through loan loss provisions.This study also controls for the effect of 2007-2009 global financial crisis on loan loss provisioning of Malaysian commercial banks.The results indicate that Malaysian commercial banks put aside more provisions during the financial crisis.